Depressive symptoms are found to be potential adverse effects of androgen deprivation therapy in older prostate cancer patients: A 15‐month prospective, observational study. Issue 12 (31st May 2017) - Zhang, Zhiqiang; Yang, Linlin; Xie, Dongdong; Shi, Haoqiang; Li, Guangyuan; Yu, Dexin
Abstract: Objectives: To evaluate the association between androgen deprivation therapy (ADT) and depression and to identify the risk factors for depressive symptoms among prostate cancer (PCa) patients who received ADT. Methods: We conducted a prospective, longitudinal, controlled study and assessed 3 groups of older patients: the ADT group (men who were presented with maximum androgen block); the radical prostatectomy (RP) group (PCa control group: men who underwent RP without ADT); and the benign prostatic hyperplasia (BPH) group (men who had BPH). All patients completed the demographic questionnaire at baseline and the Zung Self‐Rating Depression Scale (SDS) at pretreatment baseline, 1 month, 6 months, 9 months, 12 months and 15 months. Results: A total of 146 patients completed the study during the 15‐month follow‐up. The Self‐Rating Depression Scale scores of the 3 groups showed significant differences at 1 month ( P < .001), 6 months ( P = .009), 9 months ( P < .001), 12 months ( P < .001), and 15 months ( P < .001). At 9 months, 12% of the men in the ADT group, 4.3% in the RP group, and 2% in the BPH group showed depressive symptoms, and there were no significant differences ( P = .095). However, there were significant differences among the 3 groups relative to the incidence of depressive symptoms at 12 and 15 months ( P < .001, P = .007, respectively). The analysis of the ADT subgroup indicated that alcohol consumption (odds ratio = 6.868; P = .046; 95% CI, 1.038‐45.443) and smoking (odds ratio = 13.661; P = 0.013; 95% CI, 1.722‐108.386) increased the risk for developing depressive symptoms. Conclusions: Androgen deprivation therapy use does significantly increase the depressive scores and enhance the incidence of depression among PCa patients who received ADT. Smoking and alcohol consumption are associated with depressive symptoms among PCa patients receiving ADT.